The effects of online tourism information quality on conative destination image: The mediating role of resonance - Wang, Xueyi; Wang, Xin; Lai, Ivan Ka Wai (Frontiers in Psychology, 2023)
With the increasing popularity of mobile applications, people enjoy browsing online tourism information on social media. This information may cause psychological resonance, which in turn stimulates travel intentions. This study examined the relationship between online travel information quality (OTIQ), resonance, and conative destination image. A partial least squares structural equation model was used to analyze the survey data of 426 users who recently used social media to browse online tourism information. The results show that four dimensions of OTIQ (value-added, relevancy, completeness, and design) affect cognitive resonance, and three dimensions of OTIQ (interestingness, design, and amount of information) affect emotional resonance. Both cognitive resonance and emotional resonance directly affect the conative destination image. This study contributes to online tourism marketing research by identifying the factors of OTIQ that rise tourists’ resonance. It also contributes to destination image research by extending the application of resonance theory and examining the role of cognitive resonance and emotional resonance in forming a conative destination image. Understanding how QTIQ builds a destination image can help destinations improve the quality of online tourism information to attract potential tourists. This study also provides recommendations to destination marketers to formulate appropriate marketing strategies in the age of innovative technology.